Anterior deflected urinary stream in female children: description of a unique clinical entity and surgical management - Swallow, Matthew S.; Sharadin, Cynthia A.; Schaeffer, Anthony J.; Jacobson, Deborah L.; Lau, Glen A. (Frontiers in Pediatrics, 2024)
Objectives: To investigate the clinical presentation and outcomes for a series of female pediatric patients with severe anterior deflection of the urinary stream (ADUS) who were managed via urethromeatoplasty. Methods: This single institution retrospective cohort study used the institutional billing database to identify female patients <=18 years who received a urethromeatoplasty (CPT 53450) from 2007-2022. Patients were included if a substantial anterior deflection of their urinary stream was the primary indication for surgery. Patients were excluded if they were >18 years of age, had a history of prior genital trauma, or underwent surgery for an indication other than a deflected urinary stream. Results: 20 female patients underwent urethromeatoplasty between 2007 and 2022, with a median age of 3 years old. All patients presented with difficulty aiming the urinary stream during toilet training and demonstrated a web of tissue along the posterior aspect of the urethral orifice. 19/20 patients noted immediate response (i.e., normal, non-deflected urinary stream) after the urethromeatoplasty with no further urinary complaints. There were no post-operative complications within a 90-day period. Conclusions: ADUS is a clinical entity characterized by a web of deflecting tissue at the female posterior urethral meatus that causes severe urinary deflection without other urologic symptoms. This is not well-described in the literature. Surgical correction via urethromeatoplasty is safe and effective.